(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Chronic coprostasis (chronic fecal impaction) in patients with dolichomegacolon represents a challenging clinical entity characterized by abnormal colonic elongation and dilatation. When conservative management fails, surgical intervention becomes necessary. Minimally invasive surgical (MIS) approaches have emerged as preferred techniques offering potential advantages over traditional open surgery.